Tuning the rheological properties of cellulosic ionogels reinforced with chitosan: The role of the deacetylation degree. (1st March 2019) - Villar-Chavero, M. Mar; Domínguez, Juan C.; Alonso, M. Virginia; Oliet, Mercedes; Rodriguez, Francisco
Graphical abstract: Highlights: Cellulosic ionogels reinforced with chitosan were developed. The effect of the deacetylation degree on rheological properties was significant. Gel84 exhibited the greatest viscoelastic properties. Abstract: The rheological and thermal properties of formulated cellulosic ionogels reinforced with chitosan with 54–84% deacetylation degrees (DDs) were studied. The ionogels were stable, and the linear viscoelastic regions (LVRs) were determined. The rheological spectra of the ionogels revealed strong physical gels. Moreover, the effect of the DD on the viscoelastic properties was significant. The ionogel reinforced with chitosan with a DD of 84% exhibited the greatest viscoelastic properties (G': ∼10.6 kPa, G": 20.6–1.7 kPa, and η*: 200–0.05 kPa s). The ionogels exhibited the same glass transition temperature, which was approximately −98 °C, and a melting temperature of 40 °C. In addition, these materials were shown to be thermoreversible. This study provided basic rheological and thermal evidence that could be used to design new ionogels reinforced with chitosan with a specific DD for use as scaffolds for wound management.